Transepidermal water loss (TEWL): Environment and pollution—A systematic review. Issue 2 (25th February 2022) - Green, Maxwell; Kashetsky, Nadia; Feschuk, Aileen; Maibach, Howard I.
Abstract: Introduction: Transepidermal water loss (TEWL) is an objective measurement of skin integrity measured as the amount of water lost across the stratum corneum. TEWL varies greatly across variables such as age and anatomic location, and disruptions in the skin barrier have been linked to inflammatory dermatoses such as psoriasis and atopic dermatitis. Impact of environmental conditions and pollution on TEWL has yet to be determined. Accordingly, this review summarizes effects of environmental conditions and pollution on TEWL. Methods: A comprehensive literature search was performed using Embase, PubMed, and Web of Science to find human studies that provided data on environmental conditions and/or pollution and TEWL. Results: In total, 15 studies were included, with 11 studies examining environmental and seasonal conditions on TEWL and four examining pollution. All studies examining pollution showed increased TEWL in people exposed to particulate matter or NO2. Contradictory results were found on the effects of season and climate across the 11 studies, with no consensus reached. Conclusion: Exposure to pollution is reported to cause increases in TEWL, likely through free radical damage. Significant discrepancies exist among current literature as to the effects of season and climate on TEWL. There is a need to continue examining environmental variables other than temperature and relative humidity, such as atmospheric and steam pressure, that may impact TEWL. Abstract :